Assessment of Zoochemical Constituents and Antiplasmodial Potency of Crude Methanol Extract from Millipede (Diplopoda: Pachybolidae) in Plasmodium berghei Infected Mice - Kamoru Abdulazeez, Adeniyi; Adegbola Adesoye, Oluwaseun; Okunlola, L. T; Sherif M. A; D. H. , Dauda; O. Akinsete, Israel; O. Adeogun, Adedapo; A. Ezeonuegbu, Blessing; A. Akinleye, Callistus (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Malaria infection remains a major public health problem in more than 106 countries, in spite of the aggressive control over the years. Therefore, the need for alternative drugs with better efficacy and lesser proneness to resistance. This study evaluated the zoochemical constituents and antiplasmodial efficacy of the methanol extract of Millipede in Plasmodium berghei infected mice. Mice were intraperitoneally infected with Plasmodium berghei. The presence of parasite was ascertained by microscopic examination of blood samples daily. The methanol extract of millipede was administered orally for 7 days from the day parasitaemia reach 5% of parasite inoculation. The acute oral toxicity of the millipede extract was also assessed. Chloroquine was used as a positive control The millipede-treated groups were given 2 different doses (i.e., 300mg/kg and 600mg/kg) and they showed a gradual dose dependent decrease in parasitemia as well as the control group. The result of the zoochemical analysis reveals the presence of Alkaloid, saponins, Tannins, flavonoids. Alkaloid content was significantly highest (42.89) than the other phytochemicals recorded. The acute oral toxicity shows that the Median Lethal dosage is above 5000mg/kg. The maximum antimalarial activity was observed in the mice treated with chloroquine (2.00 ± 0.00) which was closely followed by millipede extract (2.27± 0.15). Millipede bioactive metabolite is novel in malaria treatment and findings from the present study recommended that it should be considered as a promising antimalaria agent.